Evaluación del grado de eutrofización de la laguna natural El Carmen y su situación con las épocas del año. - Zambrano Alcívar, Ariana Romina (2018)
The objective of the research was to determine the correlation of living photosynthetic organisms and the factors that determine growth in the natural lagoon "El Carmen" in the canton of the same name. The research was of a non-experimental type, it consisted of sampling in two epochs of the year, in the dry period that includes the months of May to November and the rainy period that goes from December to April, in which chemical, physical and biological parameters were measured, yielding pH with an average of 5; Temperatures of 25, OD of 45 Depths of 5, PT of 23 and chlorophyll "a" 456 performed in situ and also the laboratory, applying a methodology of the Carlson Trophic Status Index, which was modified by Toledo, with the data obtained from Depth, Phosphorus and Chlorophyll a was calculated the EIT of the lagoon where a general average of the trophic status index of 53.43 was obtained, which indicates that the reservoir presents a meso-eutrophic state since the Toledo classification considers that if this value is in the range of 45-55 the lagoon studied has said, therefore the aquatic species present in the reservoir, will be affected by the excess of nutrients and as a consequence the proliferation of algae in the anoxic state that cause it to run out the oxygen by the breathing and decomposition of these, causing the death by asphyxia of the organisms.